A Spatial Analysis to Permanent Income as Deterrent of Homicides: the case of Medellin City (2016)
This paper studies the relationship between permanent income and homicides, estimating an income-crime elasticity. We assume that this elasticity varies across geographical areas. We estimate different specifications of Spatial Panel Models using information of urban areas in Medellin (Colombia), areas known as communes. Spatial Models consider the importance of location and the type of neighbors of each commune. We simulate an intervention over permanent income in order to estimate the income elasticity for each commune and the average elasticity of income-crime on the city. We provide evidence about spatial dependence between the homicides per commune and their neighbors, and about a relationship between homicides and neighbor’s income. In our case of study, the average estimated impact of 1% increase in permanent income in a specific commune produces a decrease in the homicide rate on average in 0.39%. Finally, permanent income plays a crime deterrent role, but also this effect of income on crime varies across the city, showing that some areas are strategically located to this kind of intervention.